2016
DOI: 10.1016/j.celrep.2016.11.067
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Epilepsy and Autism: Disruption of GABRB3 Causes Ocular Hypopigmentation

Abstract: Reduced ocular pigmentation is common in Angelman syndrome (AS) and Prader-Willi syndrome (PWS) and long thought to be caused by OCA2 deletion. GABRB3 is located in the 15q11-13 region flanked by UBE3A, GABRA5, GABRG3 and OCA2. Mutations in GABRB3 have been frequently associated with epilepsy and autism, consistent with its role in neurodevelopment. We report here a robust phenotype in the mouse in which deletion of Gabrb3 alone causes nearly complete loss of retinal pigmentation due to atrophied melanosomes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
(38 reference statements)
1
9
0
Order By: Relevance
“…Furthermore, both transcript and protein levels of GABRB3 were not correlated with copy number in an analysis of PWS, AS, and 15q11.2-13.3 duplication syndrome postmortem brain ( Scoles et al, 2011 ). A recent study on phenotypes and gene expression patterns in a Gabrb3 deletion mouse model is also consistent with complex gene regulation, as neighboring Oca2 expression was reduced and ocular hypopigmentation observed ( Delahanty et al, 2016 ). Dysregulated gene expression of the 15q11.2-13.3 GABA A receptors is expected to have consequences for the balance of inhibitory and excitatory signals that regulate sleep, metabolism, and mood in PWS.…”
Section: Introductionsupporting
confidence: 62%
“…Furthermore, both transcript and protein levels of GABRB3 were not correlated with copy number in an analysis of PWS, AS, and 15q11.2-13.3 duplication syndrome postmortem brain ( Scoles et al, 2011 ). A recent study on phenotypes and gene expression patterns in a Gabrb3 deletion mouse model is also consistent with complex gene regulation, as neighboring Oca2 expression was reduced and ocular hypopigmentation observed ( Delahanty et al, 2016 ). Dysregulated gene expression of the 15q11.2-13.3 GABA A receptors is expected to have consequences for the balance of inhibitory and excitatory signals that regulate sleep, metabolism, and mood in PWS.…”
Section: Introductionsupporting
confidence: 62%
“…Thrombospondin-1 (THBS1) and DNA topoisomerase 3-beta-1 (TOP3B), proteins reported to be associated with various forms of epilepsy [31,33,55], were also overrepresented in SCG patients compared with IE [31,33,55]. Other notable findings included higher observation in the IE group compard to the SCG group of SLIT2 (Slit Guidance Ligand 2 protein), an extracellular matrix protein and member of the SLIT family of proteins which has a role(s) in the blood brain barrier (BBB) integrity [37,56] The mitochondrial protein MT-ND1 with epilepsy background was also found to be observed more in the IE group compared to the SCG group (40).…”
Section: Discussionmentioning
confidence: 92%
“…A PubMed/Medline literature search showed 53% of these differentially expressed proteins were related to neurological function, 36% to immune/inflammation, and 19% to seizures. Notable epilepsy/seizure related proteins (shaded cells in Table 3) include CACNA2D2 [30], THBS1 [31], VLDLR [30,32], THBS1 [31], VLDLR [32], TOP3B [33], VWF [34,35], KIF1A [36], SLIT2 [37], MT-ND1 [38], EPHB2 [39], OCA2 [40], AKAP11 [41], ADAM11 [42], MAOB [43], and VPS13D [44].…”
Section: Plos Onementioning
confidence: 99%
“…We also found that four of the six (66.7%) patients in our cohort showed hypopigmentation, which is commonly seen in PWS but not previously reported in SYS. Hypopigmentation is thought to be caused by a dysfunction of OCA2 or GABRB3 [21], not by MAGEL2, and thus it was not expected. Yet, since our cohort was initially suspected of having PWS, an inclusion bias may be present.…”
Section: Discussionmentioning
confidence: 99%